2012
DOI: 10.4049/jimmunol.1201140
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 7A Contributes to West Nile Virus Pathogenesis through TGF-β1/Smad6 Signaling

Abstract: Semaphorin 7A (Sema7A) is a membrane-associated/secreted protein that plays an essential role in connecting the vertebrate neuronal and immune systems. However, the role of Sema7A has not been elucidated in viral pathogenesis. In this study, we show that abrogation of Sema7A protects mice from lethal West Nile virus (WNV) infection. Mice lacking Sema7A showed increased survival, reduced viral burden, and less blood–brain barrier permeability upon WNV infection. Increased Sema7A levels were evident in murine ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…WNV-infected subjects with a history of severe infection have reduced numbers of Th1/Th17 cells and Tregs (31), consistent with reduced SEMA4A levels (31). The related class VII semaphorin family member SEMA7A (CD108) was previously shown to diminish WNV infection through reduced viral loads and levels of TNF-␣ mediated by transforming growth factor ␤1 (TGF-␤1)/Smad6 signaling leading to diminished blood-brain barrier permeability and lower levels of viral entry to the brain (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WNV-infected subjects with a history of severe infection have reduced numbers of Th1/Th17 cells and Tregs (31), consistent with reduced SEMA4A levels (31). The related class VII semaphorin family member SEMA7A (CD108) was previously shown to diminish WNV infection through reduced viral loads and levels of TNF-␣ mediated by transforming growth factor ␤1 (TGF-␤1)/Smad6 signaling leading to diminished blood-brain barrier permeability and lower levels of viral entry to the brain (21).…”
Section: Discussionmentioning
confidence: 99%
“…Virulent WNV (CT-2741), provided by John Anderson, Connecticut Agricultural Experiment Station, New Haven, CT (19), was passaged in Vero cells, and viral PFU were quantified by plaque assays (12). CT-2741 has been shown to be lethal in murine models of WNV infection (20,21). WNV studies were conducted in a biosafety level 3 facility licensed by the State of Connecticut and Yale University.…”
Section: Methodsmentioning
confidence: 99%
“…In the latter compartment, it localizes in part to CD4 2 Tregs were not associated with progressive IPF, it is possible that Sema 7a expression identifies a population of Tregs that traffics to the lung and contributes to disease progression via impaired suppressor capabilities and permissive effects on profibrotic inflammatory responses, although this hypothesis will require further evaluation, and other mechanisms have not been ruled out (29). Because it has also been shown that identification of CD4 1 CD28 2 cells in the blood of subjects with IPF predicts reduced event-free survival (30), it is intriguing to speculate that the Sema 7a…”
Section: Discussionmentioning
confidence: 99%
“…For example, TGF-β1’s interactions with Semaphorin 7a, a neuroimmune protein expressed on a wide variety of structural and inflammatory cells, results in enhanced myofibroblast activation and fibrosis in several mouse models [33]. Interestingly, it has also been shown that Sema 7a might regulate TGF-β1 production by monocyte-derived cells in the setting of certain viral infections [34] though the relevance of this finding to myofibroblasts in the context of lung fibrosis has yet to be explored.…”
Section: Novel Regulators Of Tgf-β1mentioning
confidence: 99%